Penerapan Model Kolaborasi Interprofesional dalam Upaya Meningkatkan Keselamatan Pasien: a Systematic Review - Keumalasari, Keumalasari; Yetti, Krisna; Hariyati, Rr. Tutik Sri (REAL in Nursing Journal, 2021)
Background: Patient Safety is a global issue that has received worldwide attention which is caused by patient safety incidents such as medical errors, medication errors, surgical procedure errors, risk of falls, ineffective communication resulting in death. To realize the quality of health services and improve patient safety, interprofessional collaboration is able to provide better care and reduce the number of patient safety incidents. Aim: To find an effective Interprofessional Collaboration Model in Efforts to Improve Patient Safety. Method: We conducted a systematic review from 2010 to 2020. Data was collected from five databases (google scholar, PMC, PubMed, Scopus, and Science Direct) with a total search result of 50,371 articles. The inclusion criteria were a focus on interprofessional collaboration in the hospital consisting of doctors, nurses, analysts, nutritionists, pharmacists, and other PPAs using the keyword “Interprofessional collaboration and patient safety”. Results: TeamSTEPPS and CRM is able to influence patient safety improvement. Conclusions: Twelve types of intervention modifications were reported according to the inclusion criteria, but in general interprofessional collaboration with Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) and Crew Resource Management (CRM) has an effect on improving patient safety effectively, able to improve the quality of care, reduce the rate of complications and errors, reduce length of care and reduce mortalityKeyword:  Interprofessional collaboration, Patient safety, Interprofessional collaboration model